THE STUDENTS’ RESPONSES TOWARD THE IMPLEMENTATION OF PICTIONARY GAME IN TEACHING VOCABULARY TO THE SEVENTH GRADE STUDENTS IN ONE OF JUNIOR HIGH SCHOOL IN CIMAHI - Indri Kartini; Evie Kareviati (PROJECT (Professional Journal of English Education), 2021)
This study is aimed to find out the students’ responses toward the implementation of Pictionary game technique in teaching English vocabulary to the seventh-grade students. The study was conducted at SMP Dharma Kartini. The students of VII C  class that consists of 38 students were selected as the participants of the research. The research used descriptive qualitative method. The data of the research was obtained from observation during the implementation of Pictionary game in the class and from the students’ interview that has conducted to 5 students. The result showed that Pictionary game technique is useful to draw the students’ motivation in learning English vocabulary. From the data of observation showed that the Pictionary game made the students more active to get involved in teaching and learning process actively. The students also showed good responses from the data of interview, they stated that learning by using Pictionary game was fun but also challenging which make them motivate in learning English. Thus, it can be concluded that Pictionary game is an attractive technique that can be used to motivate students in learning vocabulary and make the students to learn English vocabulary in a more fun and creative way.   Keywords:  Pictionary game, Vocabulary